(untitled) - Ham, C. W. (New York, 1958)
This book is intended for use in undergraduate courses of civil, mechanical and chemical engineering. Enunciation of basic concepts; Development of physical and mathematical models with interspersed numerical examples; Illustrative examples involving the application and extension of the models developed; Objective questions and exercise problems
Keywords: Mechanical engineering